Recurrent Variceal Hemorrhage in Non-Cirrhotic Portal Hypertension with Thymoma-Related Myasthenia Gravis : A Case Report - S, Jagadesh; Valentin, Mary; Sundar Sri, M.K.; Karthickeyan, K.; Shanmugasundaram, P.; Dheenadhayalan, M. (Journal of Neonatal Surgery, 2025)
Background: Extrahepatic portal vein obstruction (EHPVO) in adults is uncommon and usually is accompanied by portal hypertension but preserved liver function. Its association with thymoma-associated myasthenia gravis (MG) presents with distinct therapeutic challenges. Case Presentation: We present a 33-year-old man with EHPVO and high-risk esophageal varices that needed to be treated with repeated endoscopic variceal ligation (EVL). He also had invasive thymoma complicated by MG with high titers of acetylcholine receptor antibodies. The management was done via a multidisciplinary team including hepatology, neurology, and surgery. Beta-blockers and plasmapheresis stabilized the patient before thymectomy. Conclusion: The simultaneous management of risk of variceal bleeding and MG-associated thymoma underscores the importance of individualized, multidisciplinary care in multisystem disorders.